A copy number variant at the HPDA‐D12 locus confers compact plant architecture in cotton. Issue 4 (6th December 2020) - Ji, Gaoxiang; Liang, Chengzhen; Cai, Yingfan; Pan, Zhaoe; Meng, Zhigang; Li, Yanyan; Jia, Yinhua; Miao, Yuchen; Pei, Xinxin; Gong, Wenfang; Wang, Xiaoyang; Gao, Qiong; et al.
Summary: Improving yield is a primary mission for cotton ( Gossypium hirsutum ) breeders; development of cultivars with suitable architecture for high planting density (HPDA) can increase yield per unit area. We characterized a natural cotton mutant, AiSheng98 ( AS98 ), which exhibits shorter height, shorter branch length, and more acute branch angle than wild‐type. A copy number variant at the HPDA locus on Chromosome D12 ( HPDA‐D12 ), encoding a dehydration‐responsive element‐binding (DREB) transcription factor, GhDREB1B, strongly affects plant architecture in the AS98 mutant. We found an association between a tandem duplication of a c. 13.5 kb segment in HPDA‐D12 and elevated GhDREB1B expression resulting in the AS98 mutant phenotype. GhDREB1B overexpression confers a significant decrease in plant height and branch length, and reduced branch angle. Our results suggest that fine‐tuning GhDREB1B expression may be a viable engineering strategy for modification of plant architecture favorable to high planting density in cotton.